Current Status of Obesity: Protective Role of Catechins - Tanisha Basu; Ashley Selman; Arubala P. Reddy; P. Hemachandra Reddy (MDPI AG, 2023)
Obesity is a growing health concern in today's society. Current estimates indicate that obesity occurs in both adults and young people. Recent research also found that the Hispanic population in the U.S. is 1.9 times more likely to be overweight as compared to their non-Hispanic population. Obesity is a multifactorial disease that has a variety of causes. All current treatment options incorporate dietary changes aimed at establishing a negative energy balance. According to current scientific research, multiple factors are involved with the development of obesity, including genetic, biochemical, psychological, environmental, behavioral, and socio-demographic factors. The people who suffer from obesity are far more likely to suffer serious health problems, such as stroke, diabetes, lung disease, bone and joint disease, cancer, heart disease, neurological disorders, and poor mental health. Studies indicate that multiple cellular changes are implicated in the progression of obesity, mitochondrial dysfunction, deregulated microRNAs, inflammatory changes, hormonal deregulation, and others. This article highlights the role that oxidative stress plays in obesity and current obesity-prevention techniques with an emphasis on the impact of catechins to prevent and treat obesity.